Instytucje prawa procesowego cywilnego w kodeksie handlowym oraz kodeksie spółek handlowych - Guzewicz, Agnieszka; Jagodziński, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of this article is to identify procedural problems regarding selected regulations of the Commercial Code and the Code of Commercial Companies. The following legal issues are thoroughly analyzed: 1 rules regarding the defectiveness of the resolutions of shareholders’ meetings in capital companies; 2 “actio pro socio” action; 3 the responsibility of LLC board members related to failing to file a bankruptcy petition in due course. The authors draw attention to the existence of a negative trend consisting in the underestimation of the importance of the institutions of civil procedural law in Polish commercial law.
Keywords: kodeks handlowy; kodeks spółek handlowych; prawo procesowe cywilne; instytucje prawa procesowe cywilne